The Price Determinants of West Texas Intermediate Crude Oil - Abitur Asianto (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2019)
The crude oil West Texas Intermediate (WTI) price shock affects the international trade as well as the domestic economy of a country and becomes one of the central issues in today's international economic assessment. This study analyzed the determinants of WTI price to predict the percentage price change as result of determinant changes. It employed vector error correction model (VECM) and used the monthly data of WTI price, supply, demand, gold, S&P 500, T-Note, US dollar index and US GDP from February 1990 to July 2017. Empirical results indicated that WTI supply and demand were the determinants of WTI prices. The supply variable was a major determinant of WTI price. An increase in growth of WTI supply would lead to a decrease in growth of price. On the other hand, an increase in growth of WTI demand would lead to an increase in growth of price.Keywords: crude oil WTI, price determinants, VECM, WTI supplyAbstrak: Guncangan harga minyak mentah West Texas Intermediate (WTI) memengaruhi perdagangan internasional dan juga ekonomi domestik suatu negara dan menjadi salah satu isu sentral dalam pembahasan ekonomi internasional saat ini. Studi ini menganalisis beberapa determinan harga WTI untuk memprediksi perubahan persentase harga sebagai akibat perubahan determinan. Studi ini menggunakan vector error correction model (VECM) dan menggunakan data bulanan harga WTI, supply, demand, emas, S&P 500, T-Note, indeks dolar AS dan PDB AS dari bulan Februari 1990 sampai Juli 2017. Hasil empiris menunjukkan bahwa supply dan demand WTI adalah faktor determinan dari harga WTI. Variabel supply merupakan determinan utama harga WTI. Kenaikan pertumbuhan supply WTI akan menyebabkan penurunan pertumbuhan harga. Sebaliknya, kenaikan pertumbuhan demand WTI akan menyebabkan kenaikan pertumbuhan harga. Kata kunci: minyak mentah WTI, determinan harga, VECM, supply WTI